Kebiasaan minum dan asupan cairan remaja di perkotaan - Dodik Briawan; Tyas Rara Sedayu; Ikeu Ekayanti (Jurnal Gizi Klinik Indonesia, 2011)
Background: Human body requires water for the active and healthy life. Water is actually a nutrient, and there is a tendency that some people neglect its important roles for health. Water requirements can vary depends on physical activity, age groups, body weight, climate, and diet (energy intake).Objective: The study aimed to identify drinking habits and to assess water intake and its adequacy of teenagers in urban.Method: Cross-sectional study was conducted from May to June 2009 in high school SMAN 2 Bogor. The samples were healthy student at grade X and XI. The number of sample was 83 students which calculated based on mean estimation. Food and beverages consumption was assessed with 2 x 24 hours recall during a week-day and a week-end. Meanwhile, the last week drinking habits was collected by interviewed. Statistical analysis used here was independent t-test.Results: The average of water intake was 2582 ± 834 ml, whereas 2939 ± 922 ml for boys and 2250 ± 581 ml for girls. The total water intake was from solid foods (656 ± 265 ml) and beverages (1927 ± 704 ml). The contribution of drinking water to the total water intake was 51% for boys (1495 ml) and 58% for girls (1311 ml). The average water adequacy was 132% for boys and 111% for girls.Conclusion: The average of water intake was consider adequate in teenagers, however there was still 24.1% of them consumed less than 90% of water adequacy.